2020
DOI: 10.1093/ajhp/zxaa079
|View full text |Cite
|
Sign up to set email alerts
|

Improving transitions of care for critically ill adult patients on pulmonary arterial hypertension medications

Abstract: Purpose The purpose of this report is to describe the activities of critical care and ambulatory care pharmacists in a multidisciplinary transitions-of-care (TOC) service for critically ill patients with pulmonary arterial hypertension (PAH) receiving PAH medications. Summary Initiation of medications for treatment of PAH involves complex medication access steps. In the ambulatory care setting, multidisciplinary teams often h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…for the included study sample to fit within this effect size range for an a priori sample size calculation. [19][20][21][22][23]34 Lastly, previous stud-…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…for the included study sample to fit within this effect size range for an a priori sample size calculation. [19][20][21][22][23]34 Lastly, previous stud-…”
Section: Discussionmentioning
confidence: 99%
“…The physiology of these PH groups drastically differs from patients with group 1 PAH, which may lead to different effects with regard to fluid administration and escalation of respiratory support. A formal power calculation was not completed for the present study, but the effect size observed in the literature in the escalation of respiratory support between the general population and PH population with sepsis ranges from 10.2% to 57% allowing for the included study sample to fit within this effect size range for an a priori sample size calculation 19–23,34 . Lastly, previous studies in fluid‐sensitive populations used placement on mechanical ventilation as the definition of escalation of respiratory support 11 .…”
Section: Discussionmentioning
confidence: 99%
“…There is no uniform benefit during the acute episode, but long-term survival might be improved [ the outpatient setting. This mandates a thorough evaluation of the patient's physical, psychological, cognitive, and social ability to handle continuous parenteral infusions in the long-term and extensive and careful coordination of care [31,32].…”
Section: Right Ventricular Afterload Reductionmentioning
confidence: 99%
“…Recent research examining medication management across transitions of care has focused on medication incidents [3,8], pharmacist-led interventions [9][10][11][12] and patient and family perspectives [13,14]. Research also identifies communication breakdowns contributing to medication incidents across transitions [15,16]; yet, little is known about what influences how health professionals communicate with each other to manage medications and avoid potential breakdowns in communication across transitions.…”
Section: Introductionmentioning
confidence: 99%